Circulação da palavra e sues efeitos de sentidos no grupo de convivência entre pessoas afásicas e não afásicas da Universidade Católica de Pernambuco - Accioly, Zara Coelho de Lima (2011)
This proposal continues the research agenda beeing developed by the author and other researchers to the Group for Research in Language Sciences regarding the linguistic and psychological phenomena involved in aphasia. Aphasia is part of a neurological problem. Its study has begun in neurology field whose understanding of considered only the organic aspects. From Freud, then, by Jakobson the study of aphasia expend to other fields and it is now considered not only in its organic aspects but also psychological and linguistic. The position of theses authors guides the present research. Thus, aphasia is seen as a disturbance in the functioning of language, involving linguistic and subject factories. As a result, the aphasic one suffers from discouragement and depression, which affects the treatment. The relationship with the family also goes only greatly affected, but this relationship is critical to its reestablishment. This research aims to investigate the interaction between aphasic ones, and aphasic ones and his family, belonging to the group of living of the Catholic University of Pernambuco. The language difficulties are observed as well as its repercussions in theseinteration, besides analyzing the circulation the word among the aphasic group. Coexistence and to investigate when they drive and how welcome the word of relatives and, finally to investigate incidents stemming from subjective difficulties languages. The methodology of this work uses the line of qualitative research which consists of nine case studies. The analysis identified the linguistic quality of interaction established among aphasic ones Group Living in the Catholic University of Pernambuco, noting the difficulties of language and how those difficulties affect his objectivity on, becoming a burden, while freezes them and isolates them as a consequence of the impossibility of exercising the language. It was possible to analyze how these modify the difficulties of aphasic ones with their families